Golden state, golden youth : the California image in popular culture, 1955-1966 - May, Kirse Granat (University of North Carolina Press, 2002)
May explores the creation and dissemination of idealized images of California youth culture--broadcast, for example, through beach movies such as Gidget, TV shows such as the Mickey Mouse Club, and the music of the Beach Boys--that came to dominate the popular imagination in the 1950s and 1960s.